Problem with free boundary for the systems of equations of reaction-diffusion type - Rasulov, M. S.; Takhirov, Zh. O. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider a problem with free boundary for systems of quasilinear parabolic equations. A part of the boundary conditions are given in the nonlocal form. The a priori estimates of the H¨older norms are established. These estimates are used to prove the existence and uniqueness of the solution.